Pengaruh Kualitas Produk, Harga, Distribusi, Kualitas Pelayanan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan PT.XYZ - Willy Lesmana; Siti Nurjanah (Research and Community Service UNIVERSITAS KALBIS, 2025)
This research aims to identify the influence of product quality, price, distribution and service quality on customer satisfaction at PT. XYZ which has an impact on customer loyalty. This research uses quantitative methods using SPSS. This research technique uses survey research techniques with data collection methods with questionnaires online. The sampling technique used was the Slovin Technique with 61 respondents. This research uses validity, reliability, classical assumptions, hypotheses and path tests. In the hypothesis test, the results of the path analysis test carried out show that product quality (X1), product price (X2), distribution (X3) and service quality (X4) have an effect on customer satisfaction (Z) by 81.8%. Meanwhile, other factors 18.2% were influenced by other factors outside this research. Product quality (X1), product price (X2), distribution (X3), service quality (X4) and customer satisfaction (Z) influence customer loyalty (Y) by 40.2%. Through intervening tests, customer satisfaction can become an intervening variable.